Kajian Strategis terhadap Efektivitas Implementasi Bauran Pemasaran 7P dalam Meningkatkan Kepuasan Pelanggan dan Memperluas Pangsa Pasar di Tengah Persaingan UMKM - Dadan Hermawan; Angga Nadiyanto Prastian (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the implementation of the 7P marketing mix strategy (product, price, place, promotion, people, process, and physical evidence) in the Kopi Sukses Lima Waktu business. A good and integrated marketing mix strategy is expected to increase competitiveness and expand market share. The research method used is descriptive qualitative, with data collection through interviews with business owners and customers, as well as direct observation of business operations. The results show that Kopi Sukses Lima Waktu products have met customer needs and preferences. Good product quality is the main attraction for loyal customers. Competitive pricing, while still in line with product quality, also plays a key role in success. Selecting a strategic business location also supports an increase in the number of customers, because it is easily accessible to consumers. In terms of promotion, although the business has been carried out through social media, there are still shortcomings in maximizing digital promotion. This presents an opportunity to increase customer engagement and expand market reach. The people factor (HR) also plays a crucial role, where employee performance and their friendly attitude create a positive experience for customers. Efficient and fast operational processes in serving coffee also provide added value for customers who prioritize practicality. Physical evidence, such as packaging and product presentation, also plays a role in shaping brand image and consumer experience. Attractive packaging that aligns with the brand concept enhances the perception of product quality. In conclusion, a more integrated marketing mix strategy is urgently needed, particularly in strengthening digital promotions and managing operational processes more efficiently. Recommendations from this study include new product development, innovation in digital promotions, and improving human resource quality and customer experience management to support the growth of Kopi Sukses Lima Waktu.